Effect of Two Different Sugarcane Cultivars on Rhizosphere Bacterial Communities of Sugarcane and Soybean Upon Intercropping - Liu, Yue; Yang, Huichun; Liu, Qi; Zhao, Xiaowen; Xie, Sasa; Wang, Ziting; Wen, Ronghui; Zhang, Muqing; Chen, Baoshan (Frontiers in Microbiology, 2021)
Intercropping of soybean and sugarcane is an important strategy to promote sustainable development of the sugarcane industry. In fact, the knowledge of the interaction between the rhizosphere and bacterial communities in the intercropping system is still evolving; particularly, the influence of different sugarcane varieties on rhizosphere bacterial communities in the intercropping process with soybean, still needs further research. Here, we evaluated the response of sugarcane varieties ZZ1 and ZZ9 to the root bacterial community during intercropping with soybean. We found that when ZZ9 was intercropped with soybean, the bacterial diversity increased significantly as compared to when ZZ1was used, and ZZ9 dominated the intercropping process with soybean by affecting the diversity of rhizosphere bacteria, forming a rhizosphere environment more conducive to the growth of sugarcane. In addition, our study found that ZZ1 and ZZ9 also had significant differences in the utilization of nutrients. for example, they are affected by different functional genes in processes such as denitrification，P-uptake and transport system, inorganic P-solubilization, and organic P-mineralization. These results have significance in terms of providing guidance to the sugarcane industry, particularly for the intercropping of sugarcane and soybean in Guangxi, China.